Disruption of the OsWRKY71 transcription factor gene results in early rice seed germination under normal and cold stress conditions - Santiago Bataller; James A. Davis; Lingkun Gu; Sophia Baca; Gaelan Chen; Azeem Majid; Anne J. Villacastin; Dylan Barth; Mira V. Han; Paul J. Rushton; Qingxi J. Shen (BMC Plant Biology)
Abstract Background Early seed germination in crops can confer a competitive advantage against weeds and reduce the time to maturation and harvest. WRKY transcription factors regulate many aspects of plant development including seed dormancy and germination. Both positive and negative regulators of seed germination have been reported in many plants such as rice and Arabidopsis. Using a transient expression system, we previously demonstrated that OsWRKY71 is a negative regulator of gibberellin (GA) signaling in aleurone cells and likely forms a “repressosome” complex with other transcriptional repressors. Hence, it has the potential to impact seed germination properties. Results In this study, we demonstrate that OsWRKY71, a Group IIa WRKY gene, appeared at the same time as seed-bearing plants. Rice mutants lacking OsWRKY71 have seeds and embryos that germinate earlier than wildtype controls. In oswrky71 aleurone layers, α-amylase activity was hypersensitive to stimulation by GA3 and hyposensitive to inhibition by abscisic acid (ABA). Early germination in oswrky71 intact seeds was also hyposensitive to ABA. Transcriptomic profiling during embryo germination and early post-germination growth demonstrates that OsWRKY71 influences the expression of 9–17% of genes in dry and imbibing embryos. Compared to wildtype embryos, the mutant transcriptomes have large temporal shifts at 4, 8 and 12 h after imbibition (HAI). Importantly, many genes involved in the ABA-dependent inhibition of seed germination were downregulated in oswrky71-1. This mutant also displayed altered expression of multiple ABA receptors (OsPYLs/RCARs) that control ABA signaling and the VP1-SDR4-DOG1L branch of ABA signaling that promotes seed dormancy. Association studies reveal an OsWRKY71-containing quantitative trait locus involved in low-temperature seed germinability, qLTG-2. Indeed, oswrky71 seeds germinated early at 15 °C. Conclusions Rice Group-IIa WRKY transcription factor OsWRKY71 is a master regulator of germination that influences the expression of 9–17% of genes in dry and imbibing embryos. It is also most likely the primary candidate of low-temperature seed germinability QTL, qLTG-2. We propose that knockouts of OsWRKY71 can generate rice varieties with improved germination properties under normal or low-temperature conditions.